STUDI KRITIK MATAN HADIS: - Siti Rohmaturrosyidah Ratnawati; Ali Yasmanto (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
To determine whether a hadith is ṣāḥīḥ or not is not enough if the research is carried out only to focus on aspects of its sanad, but research on content (al-matn) of ḥadīth is also a step that should not be abandoned, because there is no guarantee that if sanad of a ḥadīth is ṣāḥīḥ (ṣāḥīḥ al-isnād), so the matn of ḥadīth is ṣāḥīḥ (ṣāḥīḥ al-matn) too. However, the studies of critics on matn al- ḥadīth have so far still tend to be few. For that reason, through this paper, the authors tried to examine about the critique of matn al- ḥadīth as an attempt to test the validity of the ḥadīth of Rasulullah Saw. from the side of its content (al-matn). A Hadith is declared as ṣāḥīḥ al-matn if it fulfills two criteria, which is avoiding syādz and free from ‘illat. The steps that can be taken to critique the content of ḥadīth are: compiling ḥadīth that are intertwined in the same theme, conducting research on content of ḥadīth with ṣāḥīḥ ḥadīth approach and approach of the Qur'an, conducting research on content of ḥadīth with language approach, and research content of ḥadīth with a historical approach.